POTENSI SUMBER DAYA ALAM DAN PENINGKATAN KUALITAS SUMBER DAYA MANUSIA DI KAWASAN MASYARAKAT PESISIR, KABUPATEN BANGKA - NFN Soewartoyo; Toni Soetopo (Jurnal Kependudukan Indonesia, 2009)
The regional autonomy gives opportunities to the local government to make policy and program regarding human resources devel9pment based on its natural resources and the needed of its society. Human resources development has a strategic position if it is directed accordingly to the natural resources potentials. This is because human resource with good quality will able to save the environment preservation. Using quantitative and qualitative approach, this article aims to describe the potential natural resources and human resource development in Bangka District. The discussed aspects would be related to the potential of the natural resources, which connected to the regional's development program, including human resource development. The results of this study show that the lack quality ofhuman resources in research area needs the improvement of education and skill. Moreover, the empowerment of society in coastal area, through skill's improvement as an anticipation of post tin-mining production in Bangka District should be done.Keywords: regional autonomy, human resources and natural resources